2012
DOI: 10.1016/j.jcmg.2012.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Reference Values for 3D Echocardiographic LV Volumes and Ejection Fraction

Abstract: These reference values are based on the largest 3DE study performed to date that should facilitate the standardization of the technique and encourage its adoption for the routine assessment of LV volumes and LVEF in the clinical echocardiography laboratory. This study supports the application of ethnicity-specific reference values for indexed LV volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 13 publications
7
69
2
1
Order By: Relevance
“…The longitudinal decrease in LV EDV and stroke volume we observed in participants who underwent follow-up is consistent with cross-sectional age relationships reported in the MESA cohort at baseline (13). More recent cross-sectional studies in healthy volunteers with three-dimensional echocardiography have shown an inverse relationship between LV volume and age (25)(26)(27). These volume relationships are in contrast to the findings of earlier studies that reported LV volume increased with age (28,29).…”
Section: Cardiac Imaging: Adverse Left Ventricular Remodelingsupporting
confidence: 86%
“…The longitudinal decrease in LV EDV and stroke volume we observed in participants who underwent follow-up is consistent with cross-sectional age relationships reported in the MESA cohort at baseline (13). More recent cross-sectional studies in healthy volunteers with three-dimensional echocardiography have shown an inverse relationship between LV volume and age (25)(26)(27). These volume relationships are in contrast to the findings of earlier studies that reported LV volume increased with age (28,29).…”
Section: Cardiac Imaging: Adverse Left Ventricular Remodelingsupporting
confidence: 86%
“…Pregnant or lactating women, athletes, and subjects addicted to alcohol were also excluded by a few authors (15,16,60), and some studies also evaluated smoking (15,21,38,82), anaemia and fever (15,16) as exclusion criteria. However, in some studies (15,19,38,43,52,54,63,82), inclusion criteria were well defined, in other sufficiently explained (20,21,24,30,50,52,61,67,70,74,76), while in few works the criteria were more generic (23,24,26,58,59,69,73).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…In particular, four major multi-center studies (the Normal Reference Range for Echocardiography-NORRE-European, The Japanese Normal Values for Echocardiographic Measurement Project-JAMP, The Echocardiographic Measurements in Normal Chinese Adults-Eminca, and The Normal Echocardiographic Measurements in a Korean population-NORMAL-trials) are currently ongoing and normative data for many 2D and a few 3D parameters have been published (15)(16)(17)(18)(19)(20)(21)(22)(23)52). Contemporary, different centers addressed the need of having normative data for new parameters coming from 3D echocardiography (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58) and deformation analysis . At present there is a big amount of echocardiographic normative data , but these data remain fragmentary and at times , difficult to find and time consuming .…”
Section: Introductionmentioning
confidence: 99%
“…Sus resultados mostraron que el ETT 2D infraestima los volúmenes del VI, pero sin diferir en FEVI. De igual manera se evidenció la influencia de la etnia en los rangos de normalidad (Chahal et al 2012). …”
Section: Aplicacionesunclassified